Quality of Service for Badan Penyelenggara Jaminan Sosial (BPJS) Participant at Syarifah Ambami Rato Ebu Hospital, Bangkalan Regency - Diana Hertati (Nusantara Science and Technology Proceedings, 2021)
Problems with health services for users of Jaminan Kesehatan Nasional (JKN) are still common, people still do not get the quality of service that meets expectations, convoluted services, and timeliness of services related to inconsistent time and procedures, and there are still unprofessional employees. in carrying out their duties. The purpose of this study was to determine the service quality of Badan Penyelenggara Jaminan Sosial (BPJS) at Syarifah Ambami Rato Ebu Hospital, Bangkalan Regency so that the community was satisfied with the services provided. The approach method used in this research is descriptive qualitative, primary, secondary data, literature study, observation, and interviews are the data sources used to explore the data. The informants in this study were the Head of Nursing Services and the Supervision and Control Section of Nursing Services and the community or patients who had used BPJS health services as their health facilities. Based on field research through interviews, it shows Badan Penyelenggara Jaminan Sosial (BPJS) Syarifah Ambami Rato Ebu Hospital, Bangkalan Regency has not been implemented properly due to 5 dimensions, namely direct (tangible), security (reliability), responsiveness (responsiveness), guarantee (assurance), and empathy (empathy). The dimensions of service quality that can be implemented satisfactorily are only reliability, assurance, and empathy. Meanwhile, for tangible and responsiveness, people are not satisfied with this dimension.